Self-organizing map (SOM) for species distribution modelling of birds species at Kenyir landscape - Salwana Mohamad Asmara; Gertrude David; Mohd Tajuddin Abdullah; Wan Isni Sofiah Wan Din; Danakorn Nincarean a/l Eh Phon; Ahmad Firdaus Zainal Abidin (International Journal of Electrical and Computer Engineering (IJECE), 2019)
Identifying which biodiversity species are more dominant than others in any area is a very challenging task. This is because of the abundant of biodiversity species that may become the majority species in any particular region. This situation create a large dataset with a complex variables to be analysed. Moreover, the responds of organisms and environmental factors are occurred in a non-linear correlation. The effort to do so is really important in order to conserve the biodiversity of nature. To understand the complex relationships that exist between species distribution and their habitat, we analysed the interactions among bird diversity, spatial distribution and land use types at Kenyir landscape in Terengganu, Malaysia by using artificial neural network (ANN) method of self-organizing map (SOM) analysis. SOM performs an unsupervised and non-linear analysis on a complex and large dataset. It is capable to handle the non-linear correlation between organism and environmental factors because SOM identifies clusters and relationships between variables without the fixed assumptions of linearity or normality. The result suggested that SOM analysis was suited for understanding the relationships between bird species assemblages and habitat characteristics.